A review of received/dominant/western film adaptation literatures, or the possibilities for a (de-westernized) Filipino theory - Arriola, Joyce L. (2018)
Access online through this link: https://www.plarideljournal.org/article/a-review-of-received-dominant-western-film-adaptation-literatures-or-the-possibilities-for-a-de-westernized-filipino-theory
Keywords: Film adaptations; Film criticism; Western films